Manual Therapy With Rest as a Treatment for Established Inflammation and Fibrosis in a Rat Model of Repetitive Strain Injury - Barbe, Mary F.; Panibatla, Siva Tejaa; Harris, Michele Y.; Amin, Mamta; Dorotan, Jocelynne T.; Cruz, Geneva E.; Bove, Geoffrey M. (Frontiers in Physiology, 2021)
Abstract Background: Repetitive strain injuries caused by repetitive occupational work are difficult to prevent for multiple reasons. Therefore, we examined the effectiveness of manual therapy with rest to treat the inflammation and fibrosis that develops through the performance of a repetitive task. We hypothesized that this treatment would reduce task-induced sensorimotor declines and neuromuscular inflammation. Methods: Twenty-nine female Sprague-Dawley rats performed a reaching and lever-pulling task for 14 weeks. All ceased performing the task at 14 weeks. Ten were euthanized at this timepoint (TASK). Nine received manual therapy to their upper extremities while resting 7 weeks (MTR); ten were assigned to rest alone (REST). Ten additional food restricted rats were included that neither performed the task nor received manual therapy (FRC). Results: Confirming previous experiments, TASK rats showed behavioral changes (forepaw mechanical hypersensitivity, reduced grip strength, lowered forelimb/forepaw agility, and noxious cold temperature sensitivity), reduced median nerve conduction velocity, and pathological tissue changes (myelin degradation, and increased median nerve and muscle inflammation and collagen production). MTR ameliorated cold sensitivity seen in REST rats, enhanced muscle IL-10 more than in REST rats, lead to improvement in most other measures, compared to TASK rats. REST rats showed improved grip strength, lowered nerve inflammation and degraded myelin, and lowered muscle TNFα and collagen I levels, compared to TASK rats, yet maintained lowered forelimb/forepaw agility and nerve conduction velocity, and increased neural fibrosis. Conclusions: In our model of repetitive motion disorder, manual therapy during rest had modest effects on behavioral, histological, and physiological measures, compared to rest alone. These findings stand in contrast to the robust preventive effects of manual therapy in this same model.